2001
DOI: 10.1042/cs20000119
|View full text |Cite
|
Sign up to set email alerts
|

The active molecular form of plasma adrenomedullin is extracted in the pulmonary circulation in patients with mitral stenosis: possible role of adrenomedullin in pulmonary hypertension

Abstract: Adrenomedullin (AM), a novel hypotensive peptide, preferentially dilates pulmonary vessels rather than systemic vessels. This suggests the possibility that AM is a circulating hormone which participates in regulation of the pulmonary circulation. A recent study revealed that two molecular forms of AM, i.e. a mature, active form of AM (AM-m) and an intermediate, inactive, glycine-extended form of AM (AM-Gly), circulate in human plasma. In the present study we investigated the production and clearance sites and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The systemic hypotensive action of AM can however be abolished after intravenous compared with intra-arterial infusion [8], suggesting that the lungs can clear circulating AM and modulate its circulating levels. Many studies have confirmed that AM is cleared by the pulmonary circulation [9][10][11][12]. The relative contribution of the lungs to AM clearance in comparison with other organs has not been systematically evaluated and, more specifically, single-pass pulmonary clearance of AM has not been quantified in vivo.…”
Section: Introductionmentioning
confidence: 92%
“…The systemic hypotensive action of AM can however be abolished after intravenous compared with intra-arterial infusion [8], suggesting that the lungs can clear circulating AM and modulate its circulating levels. Many studies have confirmed that AM is cleared by the pulmonary circulation [9][10][11][12]. The relative contribution of the lungs to AM clearance in comparison with other organs has not been systematically evaluated and, more specifically, single-pass pulmonary clearance of AM has not been quantified in vivo.…”
Section: Introductionmentioning
confidence: 92%
“…Using this kit we and other investigators found that plasma AM-T levels in normal human plasma are about 10 fmol/mL [102,106]. In hypertension, renal failure, congestive heart failure, acute myocardial infarction and pulmonary hypertension, both plasma AM-Gly and AM-m levels are increased and the ratio of AM-Gly to AM-m does not significantly change [107,101,108]. Nishikimi et al measured the two molecular forms of AM in rat cardiac tissue and plasma using this system.…”
Section: Two Molecular Forms Of Am: Mature and Glycineextended Ammentioning
confidence: 94%
“…Nishikimi et al also reported that the lung is a major site of AM clearance in man [93]. Furthermore, the same group reported that active mature AM (AM-m), a 52-amino acid peptide with a C-terminal amide structure, is specifically extracted in the pulmonary circulation [101,102].…”
Section: B Metabolic Clearance Of Ammentioning
confidence: 97%
“…We used three anti-AM monoclonal antibodies (23,24): one recognized the ring structure (rAdR-2; anti-rat AM [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]), one the C-terminal amide structure (AdC-1; anti-AM[46-52]NH2), and one the middle portion (AdM-2; anti-AM [25][26][27][28][29][30][31][32][33][34][35][36]) of the molecule. These antibodies were gifted from Shionogi & Co., Ltd., Osaka, Japan.…”
Section: Preparation Of Antibodiesmentioning
confidence: 99%
“…For rat AM-t, 10 fmol of anti AM [25][26][27][28][29][30][31][32][33][34][35][36]Fab -β-D-galactosidase conjugate (as an antibody-enzyme) was substituted for anti-AM[46-52]NH2 Fab -β-D-galactosidase conjugate, and IEMA was carried out as described above.…”
Section: Two-site Immunoenzymometric Assay (Iema) For Rat Am-m and Am-tmentioning
confidence: 99%